Perkembangan Pelabuhan Perikanan Prigi dan Dampaknya terhadap Kehidupan Sosial Ekonomi Nelayan Desa Tasikmadu, Kabupaten Trenggalek, 1978-2004 - Khoirun Nikmah; Sutejo K. Widodo; Alamsyah Alamsyah (Indonesian Historical Studies, 2018)
This article aims to analyze the development of Prigi Fishing Port and its impact on the socio-economic of fishermen community atTasikmadu Village, Trenggalek during the period 1978-2004. The Prigi Fishing Port experienced a stage of development from the Fish Landing Base (PPI) in 1978 to the Coastal Fisheries Port (PPP) in 1982, and then it was upgraded become the Nusantara Fisheries Port (PPN). The inauguration of Prigi holds in 2004. The impact of the port development affected in the socio-economic life of the coastal society in Tasikmadu. Social implications including on changes in fishing technology, work relations, and fishing catches. Meanwhile, economic impacts including changes in fishermen's income, employment, and the emergence of works opportunities.